DISABLISM AND ITS CONSEQUENCES IN KATE CHOPIN’S THE BLIND MAN - Naufal Nafis; Happy Julia Rahmadianti; Nasywa Nuzula Ramadhani; Rommel Utungga Pasopati; Kusuma Wijaya (Jurnal Citra Multidisiplin, 2026)
This study investigates disablism and its impacts in Kate Chopin’s flash fiction entitled The Blind Man. Chopin straightforwardly writes that the blind man, as the main character, is discriminated against because of his disability. This is called disablism; it occurs when people have a negative viewpoint, undermine someone with a disability, and bring harm or prolonged hatred to them. Through the theory of disablism and qualitative analysis, this research explores disablism and its impacts in both real life and literature. Chopin’s flash fiction proves that treatment toward human beings is never neutral, but always identity-related. Meanwhile, disabled people should be regarded as human beings, not through their disabilities. In conclusion, Chopin’s story opens people’s eyes to humanize others, especially those with physical limitations.